Marketing Student Perceptions of Academic Program Quality and Relationships to Surface, Deep, and Strategic Learning Approaches. (April 2021) - Faranda, William T.; Clarke, Theresa B.; Clarke, Irvine
A substantial body of empirical research outside of the marketing education literature indicates that students adopt surface, deep, or strategic learning approaches based on their learning environment, among other factors. Using the Revised Approaches to Studying Inventory and the Course Experience Questionnaire, this exploratory research examines upper-level marketing majors' learning approaches, their perceptions of the overall academic quality of their program of study, and the relationships between those two sets of indicators. Findings from 345 senior-level marketing students indicate the heaviest use of the strategic approach, followed by the deep approach, and then the surface approach. Results also suggest that strategic and deep learning approaches are associated with higher perceptions of the quality of the academic program. Surface learning is the least preferred approach and negatively associated with the perception of academic program quality and satisfaction with academic achievement. Recommendations are offered for reaching strategic learners.